STUDENTS’ WRITING ABILITY IN ONLINE ENGLISH LEARNING OF TWELFTH GRADE OF MIPA 2 OF SMA NEGERI TULAKAN IN THE ACADEMIC YEAR 2020/2021 - Pinaningsih Pinaningsih; Agung Budi Kurniawan; Agustina Sri Hafidah (The Journal Of English Teaching For Young And Adult Learners, 2022)
The objectives of the research are to find students’ writing ability in online English learning. Themethod used in the research was a case study. The researcher used the quantitative. The data weregathered from this study through tests. The subjects of this research were students of XII MIPA 2 atSMA Negeri Tulakan, who were 20 students. This research finding showed that the mean score ofstudents’ writing ability is 70.85. Then the median of students’ writing score is 66. The modus ofstudents’ writing ability is 57 and 64.The standard deviation in SMA Negeri Tulakan is 75. From thefinding and data analysis, itcan be concluded that 12 from 20 students get the score of writing understandard deviation. Then eight from twenty students get the score up to standard deviation. Most ofthem have difficulties determining ideas or content, organization or coherence text, arranginglanguage use or grammar, word choice or vocabulary, and mechanics errors, including punctuation,capitalization, and spelling. There are some data or facts about students’ ability to construct theirs.Based on the English teacher interview’s result, teaching English online learning is not going well.Both the teachers and students must be able to adapt to online learning. Another obstacle of onlinelearning is some students don’t have a cellphone that supports the online learning media. Manystudents had difficulties, such as internet network constraints and limited quotas of internet data.Students are also less interactive in English online learning.